Impact of Internal Audit by an Adequate Internal Oversight Unit on PDAM Bondowoso Regency with Good Governance - Gusti Dian Prayogi; Rudiana (Majalah Ekonomi, 2022)
The purpose of this research is to analyze the impact of Internal Audit by an Adequate Internal Oversight Unit on Regional Water Supply Companies in Bondowoso Regency with Good Governance. In this study, 36 samples of PDAM employees were taken from 40 questionnaires distributed. The research method used in this study is an analytical descriptive survey method using qualitative research. The results of this study indicate that internal audit, management of the implementation of inspection activities, follow-up activities on the results of inspections play a role in the realization of good corporate governance in PDAM Bondowoso Regency. Meanwhile, the independence, competence, and professionalism of an Internal Auditor for PDAM Bondowoso Regency did not contribute positively to the implementation of the Bondowoso Regency Water Supply Company with Good Governance. Based on the results of this study, the researchers tried to help by providing suggestions so that the Auditors (Internal Oversight Unit) at PDAM Bondowoso Regency were more independent by upholding an objective, independent and professional attitude. Bondowoso Regency should conduct testing and evaluation of the operationalization of the entire organization and operational audits that must be part of the Internal Auditor (SPI), this will help the company to achieve organizational goals, the role of the Internal Auditor (SPI) is not only as a supervisor, but also implementing overall inspection duties and tasks.